Shehu Adomian Decomposition Method for Solving Fractional Integro-Differential Equation - Nubpetchploy, Sinsup; T.Chaisuwan, Piyatida; Poltem, Duangkamol (Burapha Science Journal, 2026)
In this paper, we apply Shehu transform and Adomian decomposition method to find the approximate solution of nonlinear fractional Volterra integro-differential and fractional Volterra-Fredholm integro-differential equation. The fractional derivative is described in Caputo sense. Finally, we provide some applications to validate the efficiency and the high accuracy of this technique.